DEVELOPMENT OF DIATONIC SCALE ANDROID-BASED APPLICATION TO INCREASE INTEREST AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL - Olisna Olisna; Julia Julia; Rana Gustian Nugraha (Jurnal Cakrawala Pendas, 2024)
When learning music about diatonic scales takes place, students are less interested in learning and have difficulty, especially in distinguishing major and minor scales. The goal of this research is to create an android-based diatonic scales application. Furthermore, the purpose of this research is to examine the impact of the produced application on student interest and learning outcomes. This study used the Research and Development (R&D) research method in conjunction with the ADDIE development model with 5 research stages, namely analysis, design, development, implementation, and evaluation. The data collection techniques used in this study were expert validation questionnaires, user response questionnaires for android application learning media, and tests. The results of the material and language expert validation test received a score of 84.21% and the media expert validation received a score of 86.67%. Meanwhile, the practicality test results from the one-on-one trial scored 93.33, the small group trial 86.56%, and the field trial 92.33%. In addition, the effectiveness test showed an increase between before and after the use of android applications in learning. Thus, it can be concluded that this android-based application learning media is effectively used in the learning process so that it can increase student interest and learning outcomes.